SIMULATION OF THE THERMOMECHANICAL LOADS AND CRACKPROPAGATION OF DIFFERENT DIESEL ENGINEPISTON CROWN MATERIALS BY THE XFEM METHOD - Gherbi, M.T; Nour, A; Far3, A; Aguib, S; Djedid, T; Settet, A.T (university of eloued -جامعة الوادي, 2019)
This study concerns the dynamic behavior of the piston of a Deutz F8L413 diesel engine. The objective is to simulate by the extended finite element method (XFEM) the thermomechanical behavior of different piston materials.This study is conducted to evaluate the applied thermal loads and pressure at the end of compression. From a numerical simulation, the stresses acting on the structure and the behavior of the cracked material piston, governed by its global elastic behavior and quantified by the stress intensity factor are determined
article
Keywords: materials;cracking;stress; piston; diesel;XFEM